A TWO-COMPONENT PRODUCTION INVENTORY-ASSEMBLY SYSTEM - Yadavalli, V.S.S. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The paper considers a two-component continuous review inventory system where one of two components is produced by the organisation and the other is supplied by an outside supplier. The two components are assembled into an end product. There are two different product types. Demand occurs according to a Poisson process for each of the product types. It is assumed that product 1 is produced and its production time is arbitrarily distributed. Production is interrupted when the inventory level of product 1 reaches its maximum level. Replenishment of product 2 is done according to an adjustable reorder policy, and the lead-time follows an exponential distribution. Identifying the stochastic process as a semi-regenerative process, steady-state measures such as mean stationary rate of the number of demands lost, mean number of demands satisfied, mean number of replenishments made, are found. The total unutilised capacity of the production system is found, and a cost analysis is also studied. A numerical example is provided to illustrate the results obtained. AFRIKAANSE OPSOMMING: